Planification stratégique : 2012-2015 - Jeffery Hale - Saint Brigid's (JHSB) (2012)
Le présent document est le résultat d’une démarche entreprise par le conseil d’administration de l’Hôpital Jeffery Hale – Saint Brigid’s, il y a plus d’un an. À la suite de multiples consultations auprès de nos instances internes et externes, le conseil a élaboré les orientations stratégiques sur lesquelles nous fonderons nos actions pour les prochaines années. Elles sont présentées à nos partenaires externes suite à son adoption au printemps 2012.

Communications Assembly June 9, 2012 : Brief from the English Speaking Catholic Council - McDaid, Mary (English Speaking Catholic Council, 2012)
The English Speaking Catholic Council appreciates the opportunity to participate in this General Assembly convened by Bishop Thomas Dowd on the future of communications within the English Sector of the Archdiocese of Montreal.

Strategic Plan 2012-2017 - Coasters Association (2012)
The Lower North Shore of Québec stretches from Blanc Sablon (at the Labrador border) to Kegaska (opposite the eastern tip of Anticosti Island). Sixteen (16) communities, including the two (2) native communities of Pakua Shipi and Uanamen Shipu, are spread along 400 kilometres of rugged coastline, and in most cases are accessible only by boat, plane or snowmobile (in winter). Due to the vastness and isolation of the region, transportation costs are extremely high and often unreliable due to extreme weather conditions. This remote region, which is majority English-speaking, has witnessed a significant decline in population over the last few decades due to the collapse of the region’s main economic activity (the cod & salmon fishery), and the decline in the snow crab fishery. It is estimated that approximately half of the region’s adult population leaves the Coast at some time during the year to secure employment elsewhere. Many leave the territory for several months at a time while their family remains on the Lower North Shore which results in social dislocation as, in some cases, both parents leave for work and their children are housed with grandparents or other family members. Many social challenges have emerged from the changing circumstances, such as caring for the elderly, and many youth leave and do not return due to the lack of job opportunities.